Muscle Activity of Core Muscles During Plank Exercise on Different Surfaces - Ufuk Şekir; Huseyin Topçu; Serkan Pancar; Yakup Zühtü Birinci; Ali Kamil Güngör; Ramiz Arabacı (Selcuk University, 2022)
Determining the effects of different instability devices on core muscle activation gives important information for practitioners when prescribing strength exercises. This study aimed to compare electromyographic responses of core muscles during plank exercise performed with and without instability devices. Twenty-five subjects (age = 21.5 ± 2.66 years; height 179 ± 0.5 cm; weight 74.28 ± 4.27 kg; Body Mass Index (BMI) = 22.98 ± 1.11 kg/m2) performed plank exercise on stable surface, BOSU ball, Swiss ball, and TRX Suspension Trainer (TRX) in a crossover design. Plank exercise consisting of isometric contractions was performed two times. Surface electromyography (sEMG) was used to determine the amplitude of rectus abdominis (RA), external oblique (EO), and erector spinae (ERS) muscles during the exercise. The sEMG amplitude has been normalized against the maximum voluntary contraction (MVC) trial that yielded the highest peak torque value during isometric contractions of the related muscles. In the RA and EO muscles, significantly higher normalized sEMG amplitude (%MVC) values were detected in TRX and Swiss ball compared to a stable surface and BOSU ball (p lt;0.05). On the other hand, TRX exhibited more sEMG amplitude than the Swiss ball (p lt;0.05). A significantly higher sEMG amplitude value was detected on TRX than the Swiss ball in the ERS muscle (p lt;0.05). However, there was no significant difference between the BOSU ball and the Stable surface. In conclusion, the TRX may be a good option for those who want more challenges for the anterior and lateral core muscles. However, plank exercise seems trivial for strengthening the ERS muscle, whether on a stable surface or an instability device.